# Solve the equation `(e^x*e^(2x))/e^(x - 1) = 1` . What are the rules to be used.

*print*Print*list*Cite

Expert Answers

justaguide | Certified Educator

The equation `(e^x*e^(2x))/e^(x - 1) = 1` has to be solved.

Use the following rules: `x^a*x^b = x^(a+b)` , `x^a/x^b = x^(a-b)` and `x^0 = 1` .

`(e^x*e^(2x))/e^(x - 1) = 1`

=> `e^(x + 2x - (x - 1)) = 1`

=> `e^(x + 2x - x + 1) = 1`

=> `e^(2x + 1) = 1`

=> `e^(2x + 1) = e^0`

As the base is the same the exponent can be equated.

=> 2x + 1 = 0

=> x = `-1/2`

**The solution of the equation `(e^x*e^(2x))/e^(x - 1) = 1` is **`x = -1/2`